PENGARUH KONSELING MENYUSUI DENGAN MEDIA LEMBAR BALIK dr. UTAMI ROESLI TERHADAP PERILAKU DAN TINGKAT KONSUMSI ENERGI DAN ZAT GIZI IBU HAMIL TRIMESTER III DI DESA WANDANPURO KECAMATAN BULULAWANG KABUPATEN MALANG - Alia Wati; Sugeng Iwan Setyobudi; Astutik Pudjirahaju (Jurnal Pendidikan Kesehatan, 2019)
Cases of stunting toddlers based on Basic Health Research or RISKESDAS in 2018 amounted to 30 percent, for East Java at 33 percent, while based on the results of baseline data in Wandanpuro Village, Bululawang Malang Subdistrict in 2018 by 38 percent. To analyze the effect of breastfeeding media, Dr. Utami Roesli, counseling on behavior and consumption level namely energy and nutrients in third trimester pregnant women in Wandanpuro Village, Bululawang District, Malang Regency. This type of research is Pre experiment, using the design of One Group Pretest Posttest Design. The independent variable of this study was breastfeeding counseling with flipchart media, Dr. Utami Roesli, and the dependent variables were behavior, diet, and consumption level of third trimester pregnant women. The population in this study were 15 third trimester pregnant women in Wandanpuro Village as many as 15 people. The provision of breastfeeding media counseling, Dr. Utami Roesli, gave a significant influence on knowledge namely p equal 0.001, attitude namely p equal 0.001, skills namely p equal 0.000, eating patterns in the animal food group namely p equal 0,034, vegetables and fruit namely p equal 0,018, energy consumption level namely p equal 0,000 and fat consumption level namely p equal 0,009. There are significant differences in knowledge, attitudes, skills, diet for animal food groups, vegetables and fruit, energy and fat consumption levels. However, there are insignificant differences in the diet of grains, tubers, oils and fats, oily fruits and seeds, nuts, sugar, levels of protein and carbohydrate consumption.